Growth performance and carcass characteristics of finisher lambs maintained on intensive feeding or grazing with supplementation - KARIM, S A; VERMA, D L (The Indian Journal of Animal Sciences, 2014)
Orowth performance and carcass traits of finisher lambs were compared under intensive feeding (01) and grazing withsupplementation (02). Initial weights were higher (P